2009
DOI: 10.2527/jas.2008-1512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yeast culture supplementation on growth performance, intestinal health, and immune response of nursery pigs1

Abstract: A total of 216 weaning pigs were used in 2 experiments to determine the effects of dietary supplementation of yeast culture (YC) at different dose levels on the growth performance, nutrient digestibility, intestinal morphology, intestinal microflora, and immune response in weanling pigs and to determine whether YC can be a candidate to replace antibiotic growth promoters (AGP). In Exp. 1, 192 pigs (7.5 +/- 0.2 kg of BW) weaned at 28 d of age were randomly allotted to 6 treatments: 1) control (without AGP or YC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
266
3
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(313 citation statements)
references
References 40 publications
37
266
3
7
Order By: Relevance
“…Some studies have suggested that S. platensis (A. platensis) and S. cerevisiae could improve immunity by increasing the concentration of cytokines IFN-γ and IL-4 in newborn pigs (Shen et al 2009) and humans (Hirahashi et al 2002). However, there were no significant differences in expressions of cytokines between experimental groups were found in our study.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Some studies have suggested that S. platensis (A. platensis) and S. cerevisiae could improve immunity by increasing the concentration of cytokines IFN-γ and IL-4 in newborn pigs (Shen et al 2009) and humans (Hirahashi et al 2002). However, there were no significant differences in expressions of cytokines between experimental groups were found in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Our results demonstrate that, similarly to the findings of Salazar et al (Salazar-Monroy et al 2012), an increase in CD4+, CD8+ and CD4+/CD8+ in peripheral blood in pigs and the increase of these T lymphocyte subpopulation stimulates the antibody yield in the pigs fed 0.3% S. cerevisiae. In other studies on pigs (Shen et al 2009) the researchers added 2.5, 5, 10 and 20 g S. cerevisiae to feed, and the animals expressed a substantial development in the CD4+/CD8+ ratio in experimental groups compared to control. According to our findings and previous studies it was identified that S. cerevisiae may enhance the T lymphocyte subpopulations (CD4+, CD8+, CD4+/CD8+) and thereby improves the immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that yeast or yeast products influence blood cell composition in weanling pigs or lipopolysaccharide-challenged piglets (Davis et al, 2004;Shen et al, 2009). Davis et al (2004) found a tendency toward a lower level of neutrophils and a greater proportion of lymphocytes in blood of mannan-fed weanling pigs.…”
Section: Discussionmentioning
confidence: 99%